In Iraq, The First Application of Serological SNAP ELISA Technique In Detection of Canine Heartworms (Dirofilaria immitis) In Herder Dogs of Al-Qadisiyah and Dhi-Qar Provinces - Amal Hassan Abd AL-shabbani (Kufa Journal for Veterinary Medical Sciences, 2016)
Canine heartworm disease is one of the most pathogenic parasitic infections in the temperate countries, which had importance large effects on public health as could be infecting human. Serologically, this study is the first one in Iraq, which dealt with detection of the disease in dogs by using of SNAP ELISA technique. The overall seroprevalence for (172) herder dogs submitted to this study, was (40.12%), comprising (42.48%) and (35.59%) in Al-Qadisiyah and Dhi-Qar provinces, respectively. Also, the severity of infection in seropositive dogs had been estimated as (42.59%) for low infection level and (53.62%) for high D. immitis infection level. In association with the sex factor, the seropositive rates were (39.53%) for females and (41.86%) for males. Whilst, in relation to age factor, (32.35%) of less than 4 years dogs and (45.19%) of more than 4 years dogs, were infected, serologically. Statistically, the significant differences were showed between the seropositive results of examined provinces, intensity of infection, as well as the risk factors (age and sex) at a level of P£ 0.05.